Companions in immigrant oncology visits: Uncovering social dynamics through the lens of Goffman's footing and Conversation Analysis - Laura Sterponi; Marilena Fatigante; Cristina Zucchermaglio; Francesca Alby (Elsevier, 2024)
This paper examines the role of companions in healthcare encounters, focusing on a previously unexamined context: the oncology visit with immigrant patients. By employing a methodological approach that combines elements of Goffman's footing and Conversation Analysis, this study discerns the social dynamics and communicative patterns among doctors, patients, and companions. Our focus on the companion yields an intricate picture of their multifaceted and dynamic participation, highlighting how their roles are not predefined and stable, but rather they are co-constructed and ongoingly negotiated among participants. Specifically, our analysis reveals that while companions initially maintain a peripheral position, aligning with the oncologist's focus on the patient as the primary recipient, they readily engage in active participation when the patient recruits them or when patient recipiency is problematic. As the anamnesis progresses, our investigation highlights the significance of the companion, showing their adept moves in response to the actions of both the patient and the oncologist. Their ability to offer linguistic assistance, insights into the patient's life circumstances, and documentation of previous tests is finely tuned to the developing interaction between the oncologist and the patient. In these ways the companions contribute to a more nuanced understanding of the patient and the overall effectiveness of the visit. The study's findings have significant implications for patient-centered care, particularly in diverse healthcare settings with immigrant patients. By recognizing and leveraging companion participation, healthcare practitioners can create more inclusive and equitable healthcare practices, optimizing their contributions for patient well-being.